Frugal innovation and its application in manufacturing networks. (April 2019) - Mourtzis, D.; Zogopoulos, V.; Vlachou, K.
Abstract: The newcomer concept of Frugal Innovation is moving towards turning the drawback of resources constraints into an advantage by adapting to local market requirements, resulting in a new business model through low cost and high customer value solutions. Current literature has mainly focused on the theory and characteristics of Frugal Innovation, while only limited work regarding its practical application is observed. Therefore, this work presents a framework, which by supporting regional customization and near-optimum production network generation via advanced information and communications technology (ICT) tools, aims to facilitate the implementation of frugal innovation in manufacturing.